Civil engineering in context - Muir Wood, A. M. (Thomas Telford, 2004)
Sir Alan Muir Wood draws from his long career to place as he says 'civil engineering in context'. The book contains many personal reminiscences of his life as an engineer from early days in the Royal Navy, through his more than 25 year career as a Partner and Senior Partner with Halcrow.